165k views
1 vote
What is the answer to this math problem

What is the answer to this math problem-example-1
User Erez Hod
by
5.6k points

1 Answer

3 votes
y + x = 5x + 3
12 - y = x + 2y

Isolate x in the first equation, then substitute its expression into the second equation to find y:

y + x = 5x + 3
x = 5x - y + 3
-4x = -y + 3
x = y - 3/4

---

12 - y = x + 2y
12 - y = (y - 3/4) + 2y
48 - 4y = y - 3 + 8y
48 - 4y = 9y - 3
-4y = 9y -51
-13y = -51
y = 51/13

Substitute this into the first equation to find x:

51/13 + x = 5x + 3
x - 5x = 3 - 51/13
-4x = -12/13
x = 3/13

Lastly, substitute back into both original equations to check work;

y + x = 5x + 3 --> 51/13 + 3/13 = 5(3/13) + 3 --> 54/13 = 54/13
12 - y = x + 2y --> 12 - 51/13 = 3/13 + 2(51/13) --> 105/13 = 105/13

Answer:
x = 3/13
y = 51/13

Hope this helps.
User Croo
by
5.4k points